Expanding the Boundaries of Orthodoxy?: Friedrich Breckling and the 1687/90 German Edition of Hiel’s Works - Pietsch, Andreas (Church history and religious culture, 2018)
The article argues for a re-assessment of the widespread assumption that Friedrich Breckling should be considered the editor of the 1687/90 German edition of the works of the sixteenth-century “Familist” author Hiel. After discussing the evidence which had seemed to point towards such a role for Breckling, the article draws on unedited material to demonstrate that the Hiel edition should instead be ascribed to Loth Fischer. This sheds new light on the religious and intellectual attitudes of the heterodox Lutheran theologian Breckling. When compared to his contemporary Gottfried Arnold, Breckling not only questioned the contemporary boundaries of orthodoxy, but also re-negotiated them, integrating elements from older heterodox traditions.